Making and sustaining a difference - Haslam, Jonathan; Cowan, Jane (Clinical governance ;, 2006)
This ebook provides a collection of articles which examine successful clinical governance initiatives in action. Focusing specifically on risk management practices in relation to patient safety, the articles examine how healthcare professionals can identify and learn from mistakes, and how effective strategies can be shared globally.